Management Roles in Political and Senior Civil Servant Positions: A Multiple-Study Approach. Issue 5 (20th October 2018) - Losada, Carlos; Esteve, Marc
ABSTRACT: A recent trend in public administration studies has been to assess how public management is performed by politicians and top civil servants. Surprisingly, little is known about how these different posts develop their management roles. Following seminal management studies, we focus on core management roles to compare the ways in which politicians and top civil servants develop their management responsibilities within public organizations. Empirical evidence is provided by triangulating three separate studies developed in Spain. Results from the triangulation show that there is unmistakable evidence of differentiations between politicians and top civil servants when performing their managerial roles.